Allogenic faecal microbiota transplantation for antibiotic-associated diarrhoea in critically ill patients (FEBATRICE)-Study protocol for a multi-centre randomised controlled trial (phase II) - Cibulkova, Ivana; Rehorova, Veronika; Soukupova, Hana; Waldauf, Petr; Cahova, Monika; Manak, Jan; Matejovic, Martin; Duska, Frantisek (PloS one, 2024)
BACKGROUND: Exposure of critically ill patients to antibiotics lead to intestinal dysbiosis, which often manifests as antibiotic-associated diarrhoea. Faecal microbiota transplantation restores gut microbiota and may lead to faster resolution of diarrhoea. METHODS: Into this prospective, multi-centre, randomized controlled trial we will enrol 36 critically ill patients with antibiotic-associated diarrhoea. We will exclude patients with ongoing sepsis, need of systemic antibiotics, or those after recent bowel surgery or any other reason that prevents the FMT. Randomisation will be in 1:1 ratio. Patients in the control group will receive standard treatment based on oral diosmectite. In the intervention group, patients will receive, in addition to the standard of care, faecal microbiota transplantation via rectal tube, in the form of a preparation mixed from 7 thawed aliquots (50 mL) made from fresh stool of 7 healthy unrelated donors and quarantined deep frozen for 3 to 12 months. Primary outcome is treatment failure defined as intervention not delivered or diarrhoea persisting at day 7 after randomisation. Secondary outcomes include safety measures such as systemic inflammatory response, adverse events, and also diarrhoea recurrence within 28 days. Exploratory outcomes focus on gut barrier function and composition of intestinal microbiota. DISCUSSION: Faecal microbiota transplantation has been effective for dysbiosis in non-critically ill patients with recurrent C. difficile infections and it is plausible to hypothesize that it will be equally effective for symptoms of dysbiosis in the critically ill patients. In addition, animal experiments and observational data suggest other benefits such as reduced colonization with multi-drug resistant bacteria and improved gut barrier and immune function. The frozen faeces from unrelated donors are immediately available when needed, unlike those from the relatives, who require lengthy investigation. Using multiple donors maximises graft microbiota diversity. Nonetheless, in vulnerable critically ill patients, Faecal microbiota transplantation might lead to bacterial translocation and unforeseen complications. From growing number of case series it is clear that its off label use in the critically ill patients is increasing and that there is a burning need to objectively assess its efficacy and safety, which this trial aims. TRIAL REGISTRATION: www.clinicaltrials.gov (NCT05430269).
Keywords: průjem; Gastrointestinal Microbiome; fekální transplantace; feces; Humans; multicentrické studie jako téma; Female; Diarrhea; lidé; antibakteriální látky; dysbióza; Critical Illness; randomizované kontrolované studie jako téma; Feces; ženské pohlaví; Anti-Bacterial Agents; Male; Randomized Controlled Trials as Topic; Dysbiosis; kritický stav; Fecal Microbiota Transplantation; střevní mikroflóra; klinické zkoušky, fáze II jako téma; mužské pohlaví; prospektivní studie; Multicenter Studies as Topic; Clinical Trials, Phase II as Topic; Prospective Studies